Three globalizations, not two: Rethinking the history and economics of trade and globalization - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
The conventional wisdom is there have been two globalizations in the modern era. The first began around 1870 and ended in 1914. The second began in 1945 and is still underway. This paper challenges that view and argues there have been three globalizations, not two. The first half of the paper provides empirical evidence for the three globalizations hypothesis. The second half discusses the analytical implications of the three globalization hypothesis. The Victorian first globalization and Keynesian era second globalization were driven by gains from trade, and those gains increased industrialized country real wages. The neoliberal third globalization has been driven by industrial reorganization motivated by distributional conflict. Trade theory does not explain the third globalization; capital's share has increased at the expense of labor's; and there can be no presumption of mutually beneficial gains from the third globalization.
Keywords: F00; F10; F20; 330; Globalization; trade theory; barge economics